Electronic governance in Portugal: a silent pioneer - Fernandes, Sara Santos (2016)
This paper sums up the Portuguese experience on launching and implementing a number of successful EGOV policies at different levels. Such a success was based on a holistic understanding of EGOV, in the confluence of technology, administrative reform and innovation processes, and enforced through a number of well- defined, consistent policies carried out over time. The role of national agencies, independent from local political instances and private interests, in the implementation of an effective EGOV strategy is also stressed.